If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -5 = -8(6 + 5t) Reorder the terms: -5 + 3y = -8(6 + 5t) -5 + 3y = (6 * -8 + 5t * -8) -5 + 3y = (-48 + -40t) Solving -5 + 3y = -48 + -40t Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3y = -48 + 5 + -40t Combine like terms: -5 + 5 = 0 0 + 3y = -48 + 5 + -40t 3y = -48 + 5 + -40t Combine like terms: -48 + 5 = -43 3y = -43 + -40t Divide each side by '3'. y = -14.33333333 + -13.33333333t Simplifying y = -14.33333333 + -13.33333333t
| 11(t-3)+3t=7(2t+4)-10 | | 4x-7=-2x-19 | | 8.99(85)=650+x | | 6+25x=20x+8 | | 8(x-5)-6x=-26 | | 0.5x(y-z)= | | 5.45=14.8-2.2t | | -22=4w+2(w+4) | | y+24=11 | | 7(3x+6)=21x-10 | | (p+7)(-2)= | | -33=5(v-3)-2v | | x=-1/2*4 | | 8.99(x)=1050+335 | | -(3r-2)=-4-4r | | -5y+8=10+y | | x+3-3(5x+15)=5 | | -4+3x=-6+10x | | 12x^2y^4-3x^5+9x^3y^2=0 | | 6x+234= | | -x+33=2x+15 | | a=(3x^2y^3)(5xy^2) | | -3(1-2x)=47-x | | Solve-3(2x-9)=-3 | | 4x+6y=-132 | | 3-2x=5(3+x) | | 6+2x=2x+6 | | 9n-7=4n+8 | | 10x-50+50=-15+50 | | 23-4x=7-8x | | 12x=18-2x | | -x+1=2x+13 |